Selective Herbicides for Cultivation of Eucalyptus urograndis Clones - Patrick J. Minogue; Anna Osiecka (International Journal of Forestry Research)
Competition control is essential for successful eucalyptus plantation establishment, yet few selective herbicides have been identified. Five herbicides, flumioxazin, imazamox, imazapic, oxyfluorfen, and sulfometuron methyl, were evaluated for selective weed control in the establishment of genetically modified frost tolerant Eucalyptus urograndis clones. Herbicides were applied at two or three rates, either before or after weed emergence, and compared to a nontreated control and to near-complete weed control obtained with glyphosate directed sprays. Applications prior to weed emergence were most effective for weed control and, with the exception of imazapic, all resulted in enhanced eucalyptus growth relative to the nontreated control. Among postemergent treatments, only imazamox enhanced stem volume. Among selective herbicide treatments, preemergent 2240 g ha−1 oxyfluorfen produced the best growth response, resulting in stem volume index that was 860% greater than the nontreated control, although only 15% of the volume index obtained with near-complete weed control. Imazapic was the most phytotoxic of all herbicides, resulting in 40% mortality when applied preemergent. Survival was 100% for all other herbicide treatments. This research found the previously nontested herbicides imazamox and imazapic to be effective for selective weed control and refined application rate and timing of five herbicides for use in clonal plantations.